Sustained virologic response to second-generation direct-acting antivirals for Hepatitis C - Compri, Adriana Parise (2020)
Background: Recently, the management of patients chronically infected with the hepatitis C virus has progressed, including second generation direct-acting antivirals (DAA) that have potential to clear infection in most patients, especially genotype 1-infected patients. Objectives: Evaluate the sustained virologic response (SVR) of Hepatitis C treatment with second-generation DAAs made available by the Ministry of Health in follow-up patients of a São Paulo health service. Methods: This was a retrospective observational study, based on secondary data obtained from GAL and MEDEX systems. Briefly, 615 convenience samples were analyzed of patients who underwent second-generation DAAs treatment from June 2016 to April 2018. Demographic and clinical data were also analyzed. Results: SVR was observed in 600 treated patients (97.6%). Further, 98.4% and 94.7% of genotype 1 and genotype 3 patients, respectively, responded to treatment (P = 0.02). Among patients who did not respond to treatment, 93.3% were male, naive treatment and were treated for 12 weeks, except one genotype 1, HIV-coinfected patient who received treatment for 24 weeks. Conclusions: A high rate of SVR was found for Hepatitis C treatment with second-generation DAAs. SVR was significantly reduced in male and genotype 3-infected patients, although it still exceeded 90%. Further, HIV coinfection showed no association with reduced SVR rates (p=0.98).